Identifying Small-Scale Gradients in Sediment Stability as Early Indicators of Saltmarsh Cliff Initiation - Mason, Victoria G.; Willemsen, Pim W.J.M.; Muller, Jos R.M.; Borsje, Bas W.; van de Koppel, Johan; Bouma, Tjeerd J. (John Wiley and Sons Inc., 2025)
Saltmarsh cross-shore width is a critical determinant of the ecosystem services it can provide, particularly to what extent waves can be attenuated across its surface. Cliff initiation at the seaward saltmarsh edge typically signifies the onset of marsh retreat, causing the cross-shore marsh width and ecosystem service provisioning to be reduced. Although mechanisms for marsh retreat have been studied before, the processes and conditions under which cliffs form remain unknown, making the moment of cliff initiation unpredictable. Here, we took field measurements of sediment properties and sediment stability at comparable neighboring cliffed and non-cliffed saltmarsh edges in a meso/macro-tidal system, and compared them with flume measurements of sediment erodibility. We identified three sediment-driven conditions that, when occurring concurrently at an exposed marsh edge, increase the vulnerability of a cliff forming when exposed to a hydrodynamic trigger (wind waves or tidal currents): (a) a substantial offset (sharp difference) in sediment erodibility at the saltmarsh-mudflat interface, governed by small-scale gradients in sediment characteristics such as grain size distribution, and within this; (b) a marsh edge with near-negligible erodibility under average wave forcing and (c) site-wide sediment characteristics, such as low cohesivity, resulting in an erodible mudflat. While these conditions make marsh edges cliff prone, we discuss that other mechanisms of cliff-initiation in other parts of the world cannot be excluded. Overall, we provide insight into the role of small-scale gradients in sediment stability for driving the long-term dynamics of biogeomorphic saltmarshes, which can be used as early indicators to identify cliff-prone saltmarsh areas.
Keywords: cliff erosion; cliff formation; coastal defense; erodibility; marsh edge; nature-based solutions; Geophysics; Earth-Surface Processes